Evaluation of Pharmaceutical Service and Management of Drug, Disposable Medical Supply, and Medical Equipment for Poned of Brebes Regency - Doni Hendri; Satibi Satibi; Dwi Endarti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Government regulations number 51 of 2009 and regulation of health minister number 74 year 2016 are the reference in conducting pharmaceutical care in PHC (Primary Health Care). The objectives of this research are: 1) Evaluate service, management, 2) Identify supporting, inhibiting factor, 3) Formulate solution to improve services, management of drug, disposable medical supply, and disposable medical equipment PONED Brebes district. Descriptive research was obtained by observation of LPLPO 22 PHC PONED 2016, evaluation of conformity with DOEN, national formulary, checklists, availability, adequacy, percentage and value damaged, expiration, out-of-stock duration, in-depth interview with head of the pharmaceutical section, head of maternal and child health, head of Brebes health office to identify supporting factors, inhibiting and formulating remedial solution Basic Priority Rating Scale (BPRS). Results of research showed that 1) service, drug management, disposable medical supply, disposable medical equipment by pharmacist was 54,55-59,09%, pharmacist technician was 27,27-31,82%, non-pharmacist was 13,64%, and clinical pharmacy services had not been fully implemented. Conformity of drug, disposable medical supply, disposable medical equipment with DOEN, Fornas, checklists, drug availability and adequacy with pharmacist were higher than pharmacy technician and non-pharmacist, in which it is not sufficient. Percentage of medication time span with low pharmacist from pharmacist technician and non-pharmacist; 2) Permenkes number 74 year 2016 became the supporting factor,of service, management, lacking of pharmacist, communication within PONED internals became the obstacle factor; and 3) solution for improvement including fulfillment of pharmacist at PHC PONED, evaluation upon planning, procurement at BLUD, requests to provincial health administrative, coaching and regular training. In general, drug services and management of drug, disposable medical supply, disposable medical equipment at PHC PONED in Brebes regency have not meet the predetermined standard.